PQR is a triangle in which QM perpendicular to PR and PR square - PQ square = QR square. Prove that QM square = PM*MR
Answers
Answered by
120
Given that
PQR is a triangle and QM is perpendicular on PR
Also,
PR^2 - PQ^2 = QR^2
Now in traingle QMR
QR^2 = QM^2+MR^2
Thus fro above two equations for QR
We get
PR^2 - PQ^2 = QM^2 + MR^2
QM^2 = PR^2 - PQ^2 -MR^2
QM^2 = (PM+MR)^2 - PQ^2 - MR^2
QM^2 = PM^2 + MR^2 + 2PM*MR - PQ^2 - MR^2
QM^2 = PM^2 + 2 PM^MR - PQ^2
QM^2 = PQ^2 - QM^2 + 2PM*MR - PQ^2
thus, 2QM^2 = 2 PM * MR
Hence prooved
PQR is a triangle and QM is perpendicular on PR
Also,
PR^2 - PQ^2 = QR^2
Now in traingle QMR
QR^2 = QM^2+MR^2
Thus fro above two equations for QR
We get
PR^2 - PQ^2 = QM^2 + MR^2
QM^2 = PR^2 - PQ^2 -MR^2
QM^2 = (PM+MR)^2 - PQ^2 - MR^2
QM^2 = PM^2 + MR^2 + 2PM*MR - PQ^2 - MR^2
QM^2 = PM^2 + 2 PM^MR - PQ^2
QM^2 = PQ^2 - QM^2 + 2PM*MR - PQ^2
thus, 2QM^2 = 2 PM * MR
Hence prooved
Answered by
66
Answer:
Step-by-step explanation:
In a triangle PQR, PR2-PQ2 =QR2 and M is a point on side PR such that QM is perpendicular to PR. Prove that QM2=PM*MR
Answer.....
Given:
In ∆ PQR, PR²-PQ²= QR² & QM ⊥ PR
To Prove: QM² = PM × MR
Proof:
Since, PR² - PQ²= QR²
PR² = PQ² + QR²
So, ∆ PQR is a right angled triangle at Q.
In ∆ QMR & ∆PMQ
∠QMR = ∠PMQ [ Each 90°]
∠MQR = ∠QPM [each equal to (90°- ∠R)]
∆ QMR ~ ∆PMQ [ by AA similarity criterion]
By property of area of similar triangles,
ar(∆ QMR ) / ar(∆PMQ)= QM²/PM²
1/2× MR × QM / ½ × PM ×QM = QM²/PM²
[ Area of triangle= ½ base × height]
MR / PM = QM²/PM²
QM² × PM = PM² × MR
QM² =( PM² × MR)/ PM
QM² = PM × MR
HOPE THIS WILL HELP YOU...
Similar questions